Establishing trust protocols in mutual distrust network by consensus formation - Isirova, K.; Potii, O.; Claussen, J. (Radiotekhnika, 2019)
Any interactions between actors take place through networks of connections between them. An important goal is to ensure the security of such interactions, especially in advent of quantum computing technologies. It might be that in the post-quantum world, the avatar of verification architectures will be manifested through distributed protocols. Here we augment the discussion by explicitely drawing the analogy between distributed protocol consensus formation and consensus formation in social networks in various topologies. Hierarchical networks, in both domains, exhibit slowest timescale of consensus formation. We conclude this supports universal argument towards establishment of distributed protocol mechanisms, wherever the scaleability with network size is of relevance.